2009
DOI: 10.5664/jcsm.27604
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmacological Self-Management of Sleep Among the Japanese General Population

Abstract: S leep disturbance is known to be associated with the onset of mental disorders such as depression. It is also well known that sleep disturbance is an eventual risk factor for various somatic disorders such as diabetes mellitus, obesity, and cardiovascular disease. [1][2][3][4][5] In addition, excessive daytime sleepiness (EDS) resulting from sleep disturbance may lead to industrial and traffic accidents. [6][7][8] Thus, in developed countries, employing pertinent measures to prevent sleep disturbance is widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Meal times and school/university start times can also be relatively early in China, which may contribute to relatively more morning-preference in Chinese. Research has also shown that, for example, social activity, 27 attachment style 28 and possibly unique cultural influences 29 are related to sleep patterns and sleep regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meal times and school/university start times can also be relatively early in China, which may contribute to relatively more morning-preference in Chinese. Research has also shown that, for example, social activity, 27 attachment style 28 and possibly unique cultural influences 29 are related to sleep patterns and sleep regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Two sets of chronotype classification criteria were used. Horne and Östberg's 6 cut-off points for chronotype classification are: [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The rMEQ 19 consists of five questions, corresponding to MEQ question numbers 1, 7, 10, 18, and 19. Scores range from 4 to 25, with the following cut-offs: 4-7 (DE); 8-11 (ME); 12-17 (N); 18-21 (MM); 22-25 (DM).…”
Section: Methodsmentioning
confidence: 99%
“…Instead, many use complementary health approaches such as herbal or dietary products to promote sleep or initiate self‐help strategies such as reading or listening to music, even though the effects are not well documented. Music is a commonly used tool for sleep improvement (Aritake‐Okada, Kaneita, Uchiyama, Mishima, & Ohida, ; Urponen, Vuori, Hasan, & Partinen, ), and a Canadian study found that among individuals with insomnia disorder, 43.6% had used music to promote sleep (Morin et al., ). Therefore, it is highly relevant to clarify whether music listening can actually improve sleep or not; research indicates that there is a scientific rationale for impact of music on insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…12 Potential self-treatments include conventional pharmacological aids (e.g., sedative-hypnotics), alternative therapeutics (e.g., melatonin, herbal therapies), and nonpharmacological activities (e.g., exercise, reading). [13][14][15] Although some treatments are advantageous, other choices may be particularly detrimental, such as alcohol use. Furthermore, in geriatric care, it is critical to understand patients' treatment choices because of the potentially serious consequences of polypharmacy.…”
mentioning
confidence: 99%
“…Potential self‐treatments include conventional pharmacological aids (e.g., sedative‐hypnotics), alternative therapeutics (e.g., melatonin, herbal therapies), and nonpharmacological activities (e.g., exercise, reading) 13–15 . Although some treatments are advantageous, other choices may be particularly detrimental, such as alcohol use.…”
mentioning
confidence: 99%